The ghost of Graylock - Poblocki, Dan (Scholastic Press, 2012)
Staying with their aunts over the summer, Neil Cady, his sister Bree, and their new friends Wesley and Eric, set out to explore Greylock Hall, an abandoned psychiatric hospital which is supposed to be haunted by the ghost of Nurse Janet.